TINJAUAN YURIDIS TERHADAP KEPMENAKERTRANS NOMOR KEP.101/MEN/VI/2004 TENTANG TATACARA PERIJINAN PERUSAHAAN PENYEDIA JASA PEKERJA/BURUH TERHADAP KEBERADAAN KONTRAKTOR DAN SUB KONTRAKTOR DI PERUSAHAAN PERTAMBANGAN BATUBARA DI KABUPATEN KUTAI KARTANEGARA - Ramadansyah Ramadansyah (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
ABSTRACTCivil formal or civil law is the legal rules governing the whole of how to ensure compliance with civil law material by means of the judge. Civil law is needed to regulate how rights claims should be submitted to the court, how the court should examine and give its decision and how the decision of the court should be implemented. Procedural law does not regulate the process of law enforcement outside of court. Although not governed by the procedural law, law enforcement efforts outside the court conducted in a fair and peaceful stay is required, so that the more alternatives that can be chosen by the search for justice in menuntutkan what they are entitled.